Bibliometric analysis: Economics curriculum development in the 21st century 2015-2024 - Komang Ade Komala Savitri; Hari Mulyadi; Endang Supardi (Himpunan Pengembang Kurikulum Indonesia, 2025)
Economic curriculum development is a crucial aspect in the effort to improve the quality of education and prepare future generations to face various challenges in the 21st century. A good curriculum is designed to achieve the desired cognitive, affective, and psychomotor educational goals. This study aims to identify publications related to economic curriculum development and describe the characteristics of this research. The bibliometric Analysis method was used in this research. The results showed that the number of publications containing economic curriculum development in the 21st Century increased yearly from 2015 to 2022 and decreased from 2023 to 2024. The number of documents that contain this is still relatively small, with two papers by Budiwati. At the same time, the authors with the most citations with two citations are Budiwati and Dahlan. INA-Rxiv holds the top position as the publisher with the most four documents. New themes that emerged in this field were